“What it really takes” – A qualitative study of how professionals coproduce healthcare service with immigrant patients - Christina Radl-Karimi; Dorthe S. Nielsen; Morten Sodemann; Paul Batalden; Christian von Plessen (Journal of Migration and Health, 2022)
Background: The concept of coproduction shows great promise for meaningful partnerships between patients and health professionals. This is particularly relevant for immigrant patients who are less inclined to take an active role in consultations. The present study described health professionals’ practices and experiences of coproducing healthcare service with immigrant and refugee patients in clinical encounters. Methods: We conducted a three-phase qualitative study with immigrant and refugee patients and health professionals at an interdisciplinary outpatient clinic for immigrants and refugees with complex long-standing health problems at a Danish university hospital. First, we conducted 25 observations of consultations between seven professionals (three doctors, three nurses, one social worker) and 24 patients with varied backgrounds and health problems. Findings were discussed in a focus group and individual interviews with the migrant clinic's staff. Finally, the themes were discussed with co-researchers and revised in a member check with experienced clinicians. Data were analyzed through meaning condensation, supported by the NVivo software. Results: We identified four themes characterizing the work of health professionals in creating coproduced healthcare service: a team effort of sense-making, disentangling the chaos first, when everything fails - listen to the patient, and continuity - becoming part of the patient's story. Conclusion: Interdisciplinary work fostering values of doing what makes sense to form a positive partnership with the patient allows health professionals to act autonomously, flexibly, and creatively. Using communication tools designed around patient needs, create optimal conditions for coproduction as health professionals empathically validate and integrate patient experiences. Professionals need advanced listening and relational skills and tolerance of ambiguity and insecurity. Relational continuity facilitates long-term coproduction but also bears risks of emotional dependency.